1976
DOI: 10.1136/hrt.38.9.906
|View full text |Cite
|
Sign up to set email alerts
|

Coronary artery disease in patients dying from cardiogenic shock or congestive heart failure in the setting of acute myocardial infarction.

Abstract: Pathological findings in the heart and particularly in the coronary arteries are reported from 70 patients dying from pump failure after acute myocardial infarction. Fifty of the patients had died in cardiogenic shock, the remainder from refractory congestive heart failure. Three-vessel al., 1970;Page et al., 1971;Alonso et al., 1973). Fatal pump failure after acute myocardial infarction occurs in two distinct clinical syndromes, namely cardiogenic shock and refractory congestive heart failure. Most patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

1983
1983
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(3 citation statements)
references
References 14 publications
0
2
0
1
Order By: Relevance
“…При ИМ с подъемом сегмента ST (ИМпST) КШ развивается в среднем через 5-6 ч от начала заболевания [9], у больных ИМ без подъема ST -в среднем через 94 ч [10]. Согласно данным аутопсии, требуется потеря >40 % миокарда для развития КШ [11]. Большой вклад в развитие КШ вносят механические осложнения ИМ: разрыв межжелудочковой перегородки, отрыв или дисфункция папиллярных мышц с митральной регургитацией [12].…”
Section: основы патофизиологии и критерии диагностикиunclassified
“…При ИМ с подъемом сегмента ST (ИМпST) КШ развивается в среднем через 5-6 ч от начала заболевания [9], у больных ИМ без подъема ST -в среднем через 94 ч [10]. Согласно данным аутопсии, требуется потеря >40 % миокарда для развития КШ [11]. Большой вклад в развитие КШ вносят механические осложнения ИМ: разрыв межжелудочковой перегородки, отрыв или дисфункция папиллярных мышц с митральной регургитацией [12].…”
Section: основы патофизиологии и критерии диагностикиunclassified
“…[1][2][3] It has also been reported that up to 90% of acute coronary syndrome patients 1 presenting with cardiogenic shock have multivessel or left main disease. [4][5][6] Current American College of Cardiology/American Heart Association consensus panel recommends that in the absence of hemodynamic compromise, acute interventions during STEMI should focus on the culprit lesion (CL) only. 7 However, data on optimal coronary revascularization strategy for non-CLs in MVD in the setting of acute STEMI are scarce and ambiguous, with studies reporting variable and inconsistent results.…”
Section: Introductionmentioning
confidence: 99%
“…In the 70's, Mirowski et al 7 , in a community hospital, observed that, from 1,246 patients admitted consecutively with a diagnosis of AMI, 12% developed cardiogenic shock, with a hospital mortality rate of 87%. Comparing patients with AMI complicated by cardiogenic shock and those not in shock, the former were older, with infarction in the anterior wall, and frequent history of previous infarction, angina and HF [8][9][10] . Other studies also show that those who develop shock after hospital admission are generally diabetic, older, female patients and have a history of previous infarction, with high levels of cardiac enzymes, mainly CKMB, and anterior infarction 11,12 .…”
Section: Etiologymentioning
confidence: 99%